Pengenalan Aplikasi Perpustakaan Digital Sebagai Upaya Peningkatan Kemampuan Literasi Anak Sekolah Dasar - Dwipurwani, Oki; Susanti, Eka; Sukanda, Dian Cahyawati; Indrawati, Indrawati; Cahyono, Endro Setyo (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Basic literacy that must be developed from elementary school includes reading, writing literacy and numeracy literacy. This service activity introduced a digital library application for the reading literacy program at SDN 11 Indralaya. This service activity aims to introduce digital library applications to improve reading and writing literacy skills and increase reading sources in elementary schools. The method of implementing activities is learning assistance. The activity participants were students in grades III, IV, V, and teachers. Literacy skills were measured using a digital library application. The measurement variables involved in this activity are the variables of story type, reading duration, comprehension level, answering ability and activeness. The results of the activity showed high enthusiasm from students in using the digital library application and an increase in reading interest. The evaluation results also show that there is a high level of literacy comprehension among students, and it generally increases with the grade of the students. An increase in reading duration can have a direct impact on improving students' comprehension and an indirect impact on their answering skills. This indicates an improvement in students' reading literacy. The introduction of digital libraries can be an effective solution in expanding access to quality reading materials while encouraging the literacy skills of elementary school students in this digital era.